Improving Secondary and Local Roads in Albania : Lessons from a Programmatic Approach - Humphreys, Martin; Guxho, Artan; Ishihara, Satoshi (World Bank, Washington, DC, 2012)
Albania has made considerable progress since transition in overcoming the legacy of nearly forty years of autarky. But despite significant progress and some of the fastest rates of gross domestic product (GDP) growth in South East Europe, it remains one of the impoverished countries in Europe, with the majority of the population, and the majority of the poor, living in rural areas. These areas, despite the acknowledged links between infrastructure provision and poverty reduction, are currently poorly served by infrastructure, with the majority of the secondary and local road network in poor condition, and often impassable in inclement weather. Accordingly, in 2006, the Prime Minister established a task force to prepare a program to improve a significant proportion of the secondary and local network and requested the assistance of the World Bank to prepare, and contribute to the financing, of such a program. This transport note summarizes the experience of the World Bank and details the key factors underpinning what has became a very successful program, together with the main lessons learned.